From Play to Spiritual Formation: A Literature Review on Dolanan Anak and Its Integration into Early Islamic Education - Suhendro, Eko (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines traditional Javanese children’s games (dolanan anak) as cultural artifacts that carry the potential for integrative Islamic pedagogy, particularly in embedding the values of tauhid (monotheism) and tazkiyatun nafs (spiritual purification) in early childhood education. Utilizing a qualitative library research method with a hermeneutic-thematic and ethnopedagogical approach, the research analyzes six classical Javanese manuscripts—Serat Centhini (1814), Javanesche Kinderspelen (1912), Serat Rarya Saraya (1913), Javaansche Meisjesspelen en Kinderliedjes (1930), KBG 926–928 (1930), and Dolanan ing Klaten (1942). The findings reveal that games such as sluku-sluku bathok, cak ingkling, cublak-cublak suweng, and gobag sodor not only develop children’s motor, cognitive, emotional, and social skills but also embody spiritual values such as honesty (amanah), patience (sabr), compassion (rahmah), and discipline. From the perspective of Islamic pedagogy, dolanan can be reconstructed as a medium for internalizing tauhid-based values through the reinforcement of fitrah (natural disposition), social ethics, and worship in interpersonal relations (mu’amalah). Games that involve self-control, deliberation, and cooperation align with the principles of tarbiyah Islamiyah as reflected in Surah Luqman [31]:13–19 and Surah At-Tahrim [66]:6. Traditional games also function as ta’dib (ethical cultivation) and tazkiyah when accompanied by Islamic narratives, prophetic exemplars, or short prayers integrated into play contexts. This study affirms that Javanese children’s games contain symbolic meanings aligned with Islamic values and can be adapted into early childhood curricula based on the integration of culture and religion. The findings pave the way for developing prophetic learning models that balance local cultural heritage and spiritual education, serving both as educational innovation and cultural preservation. Empirical validation in contemporary early childhood settings is needed to strengthen the contribution of this model to contextually grounded and holistic Islamic education.